2013
DOI: 10.3109/1061186x.2013.860981
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the selectivity of nanoparticle-based photoinduced damage in free and xenografted chorioallantoïc membrane model

Abstract: Background: Photodynamic therapy (PDT) is a minimally invasive treatment modality for selective destruction of tumours. Critical anatomical structures, like blood vessels in close proximity to the tumour, could be harmed during PDT. Purpose: This study aims to discriminate the photoinduced response of normal and cancerous tissues to photodamage induced by liposomal formulations of meta-tetra(hydroxyphenyl)chlorin (mTHPC). Methods: Normal vascular and cancerous tissues were represented, respectively, by free an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…A second generation PS, m ‐THPC (meta‐tetra[hydroxyphenyl]chlorin), has also been used in a PEGylated liposome formulation . Aggregation of m ‐THPC with the lipid shell of the liposomes was observed and triggered the release of m ‐THPC in the form of the monomeric photoactive state once the liposome was degraded.…”
Section: Light‐responsive Liposomesmentioning
confidence: 99%
“…A second generation PS, m ‐THPC (meta‐tetra[hydroxyphenyl]chlorin), has also been used in a PEGylated liposome formulation . Aggregation of m ‐THPC with the lipid shell of the liposomes was observed and triggered the release of m ‐THPC in the form of the monomeric photoactive state once the liposome was degraded.…”
Section: Light‐responsive Liposomesmentioning
confidence: 99%
“…PS can also be topically applied to the xenografted tumours on the CAM. The advantages of this model include the ease of in vivo microscopy to study PDT-induced vascular damage and the lack of regulatory controls on experiments involving eggs [ 7 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that at a DLI of 1 h, tumor accumulation and PDT-induced antitumor effects in terms of necrosis area were better with Fospeg ® than Foslip ® . Additionally, Fospeg ® was found to be less destructive on normal vasculatures [161].…”
Section: Nms-facilitated Treatment Modalitiesmentioning
confidence: 97%
“…Bright field microscopy is also extensively used for histological analyses of the harvested tumor and tissues from the embryo. Reagents such as hematoxylin and eosin (H&E; Figure 4(b)), or trichrome stains are applied to distinguish the cellular organelles and stromal components, and to evaluate the conditions of the tumor and TME after treatment [50,156,161].…”
Section: Imaging Of the Tumor And Vascular Networkmentioning
confidence: 99%
See 1 more Smart Citation